Respostas

2013-12-16T04:11:19-02:00
Ai é Pitagoras
o quadrado da hipotenusa vai ser igual a soma do quadrado dos catetos...
a) x² = 28² + 21²
x² = 784 + 441
x² = 1225
x = √1225
x = 35
b) 25² = 24² + x²
625 = 576 + x²
625 - 576 = x²
x = √49
x = 7
c)11² = 5² + x²
121 = 25 + x²
x² = 121 - 25
x = √96
x = √2².2².2.3 (forma fatorada da raiz)
x = 2.2√2.3
x = 4√6
d) x² = (√10)² + (√10)²
x² = 10 + 10
x = √20
x = 2√5
e) (√29)² = 5² + x²
29 = 25 + x²
x = √4
x = 2
f) x² = 32² + 24²
x² = 1024 + 576
x = √1600
x = 40
1 5 1